Study of the Role of Ultra-Processed Food (UPF) on the Risk of Obesity in Adolescents: An Observational Study in the Adolescent Community in Jambi City, Indonesia - Heri Yanto Putra; Santoso, Alexander Halim (Community Medicine and Education Journal, 2024)
Obesity in adolescents is an increasingly worrying global health problem. Unhealthy eating patterns, especially consumption of ultra-processed foods (UPF), are thought to be one of the main risk factors. This study aims to examine the relationship between UPF consumption and the risk of obesity in adolescents in Jambi City, Indonesia. Cross-sectional observational research was conducted on 350 adolescents aged 13-18 years in Jambi City. UPF consumption data was collected using the NOVA questionnaire, while anthropometric data (height, weight) was measured directly. Logistic regression analysis was used to examine the relationship between UPF consumption and the risk of obesity, with adjustment for potential confounding variables such as gender, age, and socio-economic status. The results showed that high UPF consumption (above the median 4.2 servings/day) significantly increased the risk of obesity in adolescents in Jambi City (OR = 2.87; 95% CI: 1.65-4.98; p < 0.001). This relationship remained significant after adjusting for confounding variables. No significant relationship was found between gender, age, and socioeconomic status with the risk of obesity. High UPF consumption is an independent risk factor for the incidence of obesity in adolescents in Jambi City. Comprehensive public health interventions are needed to reduce UPF consumption and promote healthy eating patterns in adolescents.